The role of autophagy in cancer: from molecular mechanism to therapeutic window - Jalali, Pooya; Shahmoradi, Arvin; Samii, Amir; Mazloomnejad, Radman; Hatamnejad, Mohammad Reza; Saeed, Anwaar; Namdar, Afshin; Salehi, Zahra (Frontiers in Immunology, 2025)
Autophagy is a cellular degradation process that plays a crucial role in maintaining metabolic homeostasis under conditions of stress or nutrient deprivation. This process involves sequestering, breaking down, and recycling intracellular components such as proteins, organelles, and cytoplasmic materials. Autophagy also serves as a mechanism for eliminating pathogens and engulfing apoptotic cells. In the absence of stress, baseline autophagy activity is essential for degrading damaged cellular components and recycling nutrients to maintain cellular vitality. The relationship between autophagy and cancer is well-established; however, the biphasic nature of autophagy, acting as either a tumor growth inhibitor or promoter, has raised concerns regarding the regulation of tumorigenesis without inadvertently activating harmful aspects of autophagy. Consequently, elucidating the mechanisms by which autophagy contributes to cancer pathogenesis and the factors determining its pro- or anti-tumor effects is vital for devising effective therapeutic strategies. Furthermore, precision medicine approaches that tailor interventions to individual patients may enhance the efficacy of autophagy-related cancer treatments. To this end, interventions aimed at modulating the fate of tumor cells by controlling or inducing autophagy substrates necessitate meticulous monitoring of these mediators’ functions within the tumor microenvironment to make informed decisions regarding their activation or inactivation. This review provides an updated perspective on the roles of autophagy in cancer, and discusses the potential challenges associated with autophagy-related cancer treatment. The article also highlights currently available strategies and identifies questions that require further investigation in the future.